INCIDENCE OF RIGHT VENTRICULAR INFARCTION IN PATIENTS WITH ACUTE INFERIOR WALL INFARCTION - Memon, Abdul Ghaffar; Shah, M Iqbal; Devrajani, Bikha Ram; Baloch, Saira (Journal of Postgraduate Medical Institute, 2015)
Objectives: To find out the frequency of right ventricular infarction (RVI) in patients with acute inferior wall myocardial infarction and also to see its clini-cal correlation and prognostic value. Methods: 198 consecutive patients with acute inferior wall myocardial infarc-tion (MI) were enrolled. Elevated ST segments in V4R or V3R to V6R were used to diagnose RVI. We assessed the incidence of ST-segment elevation in these leads and their correlation on clinical ground. Result: In 96 patients (48.5%), RVI was present. Clinical correlation showed that raised JVP was present in 58.5% and raised JVP with hypotension in 34.5% of patients. Normal JVP was present in 41.5% of patients in which 22% of pa-tients were with hypotension and 20% of patients were without clinical find -ings. Hypotension observed in 53% of patients. Complications were higher in patients with elevated ST segments in V4R (51%) in contrast to those without RVI (21%). In-hospital mortality was more than double in RVI Group. Conclusion: RVI in acute inferior MI is common. Elevated ST segments in V4R or V3R to V6R can be used to diagnose RVI. Clinical correlation can help but may not be diagnostic and it has higher mortality compared to inferior MI alone.